MicroRNA expression in antiphospholipid syndrome: a systematic review and microRNA target genes analysis - Muhammad Shazwan, S; Muhammad Aliff, M; Asral Wirda, AA; Hayati, AR; Jameela, S; Maizatul Azma Masri; Nur Syahrina Rahim; Nazefah Abdul Hamid; Nur Fariha Mohd Manzor (Malaysian Journal Pathology, 2024)
Indexed by Scopus